2022
DOI: 10.3389/fped.2022.878099
|View full text |Cite
|
Sign up to set email alerts
|

Different Frequency Bands in Various Regions of the Brain Play Different Roles in the Onset and Wake-Sleep Stages of Infantile Spasms

Abstract: Objective:The study aimed to identify the signatures of brain networks using electroencephalogram (EEG) in patients with infantile spasms (IS).MethodsScalp EEGs of subjects with IS were prospectively collected in the first year of life (n = 8; age range 4–8 months; 3 males, 5 females). Ten minutes of ictal and interictal EEGs were clipped and filtered into different EEG frequency bands. The values of each pair of EEG channels were directly compared between ictal with interictal onsets and the sleep-wake phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This builds upon previous studies that explore connectivity in IS, 29,30 and relation of sleep-wake transitions in IS. [31][32][33] Our finding that IS are associated with increased HFO connectivity is supported by previous studies that identify both the presence of ictal HFOs, 6,34,35 and their coherence 8 as biomarkers for epilepsy. By comparing pre-and post-onset, we found that the fast ripple networks may be more specific to the behavioral onset.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This builds upon previous studies that explore connectivity in IS, 29,30 and relation of sleep-wake transitions in IS. [31][32][33] Our finding that IS are associated with increased HFO connectivity is supported by previous studies that identify both the presence of ictal HFOs, 6,34,35 and their coherence 8 as biomarkers for epilepsy. By comparing pre-and post-onset, we found that the fast ripple networks may be more specific to the behavioral onset.…”
Section: Discussionsupporting
confidence: 87%
“…The anteroposterior gradient was also observed in arousals and awake states in controls suggesting that arousal networks might be related to the formulation of spasm‐related anteroposterior gradient in fast ripple hub connectivity. This builds upon previous studies that explore connectivity in IS, 29,30 and relation of sleep–wake transitions in IS 31–33 …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Detailed introduction to the BFN of patients with IESS, based on graph theory combined with Weighted Phase Lag Index (wPLI), can be found in our previous study (12) and Supplementary Table S1. CPL represents the average path length of all nodes in the network, indicating the information transmission capability of the whole-brain network.…”
Section: Eeg Data Acquisition and Preprocessingmentioning
confidence: 99%
“…High-frequency scalp oscillations have proven to be efficacious biomarkers for gauging the effectiveness and prognostic capacity of ACTH therapy in IESS patients (7). The transmission capacity of fast waves, defensive prowess, and local connectivity of slow waves all manifested an enhancement during IESS ictal onset (12). Nevertheless, the exploration of BFN alterations in children diagnosed with IESS, contrasted with healthy infants, remains inadequate.…”
Section: Introductionmentioning
confidence: 99%